The Influence of Discount and Free Shipping Tagline at Purchasing Decisions for Wardah Products on Undergraduate Management Students at Regular C, Pasim National University - Andri Asoka Sidantara Rosadi; Annisa Aulia Ramadhan; Andini Aprilianti (International Journal of Scientific Multidisciplinary Research, 2024)
This study, involving Undergraduate Management Regular Class C students, examines the impact of discounts and free shipping tagline on Wardah product purchasing decisions. It employs descriptive and associative    research    methods,         focusing         on individual students as the unit of analysis. The sample comprises 63 respondents selected using a census method. Data analysis utilizes multiple linear regression to assess the influence of these variables. The research instrument, a questionnaire, underwent validity and reliability testing. Findings indicate a significant influence of both independent variables, individually and collectively, on the purchasing decisions of the students involved in using Wardah products